Diversity of vascular epiphytes in remnant trees of the genus Ficus (Moraceae) in silvopastoral systems of southeastern Mexico - Trejo-Cruz, Iray Atziri; Martínez Camilo, Rubén; Martínez-Meléndez, Nayely; Jiménez-López, Derio Antonio (Instituto de Ecología, A.C., 2021)
Background and Aims: In silvopastoral systems, it is possible to find remnant trees that provide habitat and resources for different groups of organisms. This study analyzed the role of remnant trees of the genus Ficus (Moraceae) as refuge to harbor vascular epiphytes in the Depresión Central de Chiapas (Mexico). Methods: The presence of vascular epiphytes in three silvopastoral systems (two with extensive and one with intensive grazing) and two sites of semi-conserved tropical deciduous forest was assessed. In each site, mature Ficus trees (20-30 individuals) were selected, and all vascular epiphytes were sampled (including hemi-epiphytes). An analysis of variance was conducted in order to determine differences in richness and alpha diversity (exponential of the Shannon index) among the sites, as well as a multivariate analysis to observe changes in species composition. Key results: We found 77 species, distributed in 36 genera and nine families. The most abundant families were Orchidaceae, Bromeliaceae and Cactaceae. On average, ca. six epiphyte species were found per tree (maximum 19). Alpha diversity was higher in semi-conserved forests of both localities than in remnant trees present in the silvopastoral systems. Species composition is heterogeneous and different among sites of the semi-conserved forest and the silvopastoral systems. Half of the epiphyte species were exclusive to a determined site, mainly in the semi-conserved forest with 15 species. Conclusions: Ficus trees present characteristics, such as rugose bark texture, as well as thick and almost horizontal branches, that facilitate the colonization of epiphytes and they serve as habitat relicts in silvorpastoril systems. Therefore, they contribute to the maintenance of the total diversity of vascular epiphytes in highly modified landscapes.